The Effect of Perceived Benefit and Perceived Risk towards Fintech Continuance Intention of E-Wallet - Mega Brilliant Chandra; Cliff Kohardinata (Universitas Ciputra Surabaya, 2021)
E-wallet is one of the products of financial technology service that is developing in Indonesia recently. The tight competition of e-wallet companies can threaten the existence of e-wallet companies’ themselves due to the difficulty to maintain the users to use continuously. The purpose of this research is to find out the effect of perceived benefit on fintech continuance intention and the effect of perceived risk on fintech continuance intention. The type of this research is quantitative research. The population of this research is people who are/ have ever used e-wallet. The total sample that is used in this research is 133 respondents. Data analysis uses SPSS 22 program to do data calculations. The result of the research expresses that perceived benefit affect positive and significant towards fintech continuance intention on e-wallet, whereas perceived risk doesn’t affect significant towards fintech continuance intention on e-wallet.